Water pollution due to pesticide use in agricultural areas - Abdeljawad, Nour Salah (Environmental and Toxicology Management, 2024)
Water pollution due to pesticide use in agricultural areas is an increasingly pressing environmental issue. Pesticides are used to control pests and plant diseases, often having negative consequences for water quality and aquatic ecosystems. Method: systematic methodological approach. This study uses a descriptive method to describe the level of river water pollution due to pesticide use. Selection of locations in rivers affected by agricultural activities. Results: Decreased Water Quality, Water quality parameters such as BOD (Biochemical Oxygen Demand) and COD (Chemical Oxygen Demand) often exceed the established quality standards. As in the Babon River, BOD and COD levels show an increase from upstream to downstream, reflecting the negative impacts of agricultural activities. Conclusion: the application of sustainable agricultural practices and farmer education, the negative impacts of this pollution can be minimized, thereby maintaining environmental quality and public health. To reduce water and soil pollution due to pesticides in agriculture, several measures can be applied such as pesticide precision, Integrated Pest Management (IPM), and environmentally friendly pesticides. Manage pesticide waste safely, use bioremediation and phytoremediation, and increase farmer awareness.